Antioxidant Capacity of Carotenoid Extracts from the Haloarchaeon Halorhabdus utahensis - Ismene Serino; Giuseppe Squillaci; Sara Errichiello; Virginia Carbone; Lidia Baraldi; Francesco La Cara; Alessandra Morana (MDPI AG, 2023)
Herein, we report on the production, characterization, and antioxidant power assessment of carotenoids from the haloarchaeon Halorhabdus utahensis. It was grown at 37 °C and 180 rpm agitation in halobacteria medium supplemented with glucose, fructose, and xylose, each at concentrations of 0.2%, 1%, and 2%, and the carotenoid yield and composition were investigated. The microorganism produced the carotenoids under all the conditions tested, and their amount followed the order glucose < xylose < fructose. The highest yield was achieved in 2% fructose growth medium with 550.60 ± 7.91 μg/g dry cell and 2428.15 ± 49.33 μg/L. Separation and identification of the carotenoids were performed by RP-HPLC and HPLC/APCI-ITMSn. Bacterioruberin was the main carotenoid detected and accounted for 60.6%, 56.4%, and 58.9% in 2% glucose, 1% xylose, and 2% fructose extracts, respectively. Several geometric isomers of bacterioruberin were distinguished, and representatives of monoanhydrobacterioruberin, and bisanhydrobacterioruberin were also detected. The assignment to cis-isomers was attempted through analysis of the UV/Vis spectra, intensity of cis peaks, and spectral fine structures. The extracts exhibited superoxide scavenging activity higher than butylhydroxytoluene, ascorbic acid, and Trolox, selected as antioxidant references. The anti-hyaluronidase capacity was investigated, and the 2% fructose extract showed the highest activity reaching 90% enzyme inhibition with 1.5 μg. The overall data confirm that Hrd. utahensis can be regarded as an interesting source of antioxidants that can find applications in the food and cosmetic sectors.